Upaya Meningkatkan Kemampuan Menyimak Cerita Rakyat Siswa Kelas V SDN 16 Air Saleh Kabupaten Banyuasin melalui Pendekatan Pembelajaran Kontekstual - Subriyanto Subriyanto (Universitas PGRI Palembang, 2016)
The purpose of this study was to improve listening skills on folklore through contextual learning approach to 5th grade students at SD N 16 Air Saleh Banyuasin district. The research method used classroom action research (PTK). The subjects in this study were the students of 5th grade at SD N 16 Air Saleh totaling 28 people. Data collection techniques were done in the form of observational research, documentation and testing. Data analysis techniques of observation and listening skills tests of folklore. Based on data analysis was shown that students were succeed in listening folklore in the second cycle that has reached 85%, which means learning to listen to folklore through contextual learning approach in the second cycle has been successful or otherwise meet the criteria established. Based on the results of the study concluded that there is an increased ability to listen to folklore through contextual learning approach in 5th grade students at SD N 16 Air Saleh Banyuasin district. Keywords: ability, listening, folklore, Contextual Teaching and Learning